AMPK S-sulfuration contributes to H2S donors-induced AMPK phosphorylation and autophagy activation in dopaminergic cells. (November 2021) - Hou, Xiao-Ou; Tu, Hai-Yue; Qian, Hai-Chun; Li, Qian; Yang, Ya-Ping; Xu, Guo-Qiang; Wang, Fen; Liu, Chun-Feng; Wang, Ya-Li; Hu, Li-Fang
Abstract: Hydrogen sulfide (H2 S) serves as a neuromodulator and regulator of neuroinflammation. It is reported to be therapeutic for Parkinson's disease (PD) animal and cellular models. However, whether it affects α-synuclein accumulation in dopaminergic cells, the key pathological feature in PD, is poorly understood. In this study we reported that exogenous H2 S donors NaHS and GYY4137 (GYY) enhanced the autophagy activity, as indicated by the increases of autophagy marker LC3-II expression and LC3 dots formation even during lysosome inhibition in dopaminergic cell lines and HEK293 cells. The enhancement of H2 S donors on autophagic flux was mediated by adenosine 5′-monophosphate-activated protein kinase (AMPK)-dependent mammalian target of rapamycin (mTOR) inhibition, as H2 S donors activated AMPK but reduced the mTOR activity and H2 S donors-induced LC3-II increase was diminished by mTOR activator. Moreover, point mutation of Cys302 into alanine (C302A) in AMPKα2 subunit abolished the AMPK activation and mTOR inhibition, as well as autophagic flux increase elicited by NaHS. Interestingly, NaHS triggered AMPK S -sulfuration, which was not observed in AMPK C302A -transfected cells. Further, NaHS was able to attenuate α-synuclein accumulation in a cellular model induced by dopamine oxidized metabolite 3, 4-dihydroxyphenylacetaldehyde (DOPAL), and this effect was interfered by autophagy inhibitor wortmannin and also eliminated in AMPK Cys302A-transfected cells. In sum, the findings identified a role of Cys302 S -sulfuration in AMPK activation induced by exogenous H2 S and demonstrated that H2 S donors could enhance the autophagic flux via AMPK-mTOR signaling and thus reduce α-synuclein accumulation in vitro . Highlights: H2 S enhanced the autophagic flux in dopaminergic cells. AMPK-mTOR signaling mediated the effect of H2 S on autophagy. H2 S triggered AMPK S -sulfuration at Cys302. AMPK S -sulfuration contributed to H2 S-induced autophagy activation. H2 S donor attenuated α-syn aggregation in vitro by activating AMPK-dependent autophagy.